2018
DOI: 10.1371/journal.pone.0194844
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multi-platform meta-analysis of gene expression profiles in pancreatic ductal adenocarcinoma patients for identifying novel diagnostic biomarkers

Abstract: Applying differentially expressed genes (DEGs) to identify feasible biomarkers in diseases can be a hard task when working with heterogeneous datasets. Expression data are strongly influenced by technology, sample preparation processes, and/or labeling methods. The proliferation of different microarray platforms for measuring gene expression increases the need to develop models able to compare their results, especially when different technologies can lead to signal values that vary greatly. Integrative meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Here, we not only pointed five genes independently differentially expressed among datasets but also created an automatic tool to classify the samples and give the probability of being normal or PDAC. In contrast with the list of five differentially genes reported by Irigoyen et al 2018 [77], the CG list reported here did not include any of these genes.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Here, we not only pointed five genes independently differentially expressed among datasets but also created an automatic tool to classify the samples and give the probability of being normal or PDAC. In contrast with the list of five differentially genes reported by Irigoyen et al 2018 [77], the CG list reported here did not include any of these genes.…”
Section: Discussionmentioning
confidence: 66%
“…The datasets used in both works are different, with this in mind, sample preparation or microarray technologies (Affymetrix and Illumina) could be possible explanations to different gene lists. Furthermore, the use of ten datasets here in contrast with two datasets by Irigoyen et al 2018 [77] could also produce different results. Another explanation for these differences in the gene list presented here could be due to PDAC subtypes already studied in gene expression and clinical level [10].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since the gene expression datasets of PBMCs were related to different platforms, we merged the data through cross-platform normalization algorithms [23] to (1) increase sample sizes and improve genes signature selection [23,[31][32][33][34]; (2) appraise the heterogeneity of the overall estimate, and 3decrease the effects of individual study-specific biases [23,34]. Finally, we integrated all datasets related to the same platform and built three major datasets from Hitachisoft, Affymetrix and Illumina.…”
Section: Cross-platform Normalizationmentioning
confidence: 99%
“…Blood and saliva GEO data veri cation: We investigated a validation by comparing the key genes mRNA standardized values in ve independent GEO datasets: four of which were from blood samples (GSE74629 [16], GSE49641 [17], GSE49515 [18] and GSE15932), and the last one was from saliva samples (GSE14245 [19]).…”
Section: Data Validationmentioning
confidence: 99%